Direct write printing of a self-encapsulating liquid metal–silicone composite. Issue 28 (2nd July 2020) - Neumann, Taylor V.; Facchine, Emily G.; Leonardo, Brian; Khan, Saad; Dickey, Michael D.
Abstract : Silicone composites featuring inclusions of liquid metal particles are soft and stretchable materials with useful electric, dielectric, mechanical, and thermal properties. Abstract : Silicone composites featuring inclusions of liquid metal particles are soft and stretchable materials with useful electric, dielectric, mechanical, and thermal properties. Until recently, these materials have primarily been cast as films. This work examines the possibility of using uncured liquid metal–elastomer (LME) composites as inks for direct writing. The liquid metal inclusions act as rheological modifiers for the silicone, forming a gel-structure that can be extruded from a nozzle and hold its shape after printing. Additionally, by tuning the particle size, larger particles in the printed structures can settle to form metal-rich regions at the bottom of the structures, encased by metal-depleted (insulating) regions. Using mechanical force, the liquid metal-rich interior can be rendered conductive by sintering without affecting the insulating exterior. Thus, it is possible to print this soft and stretchable material while creating conductors with self-insulating shells.